Population dynamics of tax avoidance with crowding effects - Johannes Lorenz (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2017)
There are two ways for taxpayers to avoid paying taxes: legally, through tax optimization and illegally, through tax evasion. The government reacts by altering the law, and by conducting audits, respectively. These phenomena are modeled as a population game, a strategic interaction between all taxpayers: the more taxpayers optimize, the lower the optimization result as a consequence of the government tightening the tax law. The more taxpayers evade, the higher the risk of detection because of the tax agencies increasing the audit probability. If the government reacts to changed optimization behavior with too large a delay, an equilibrium tax law cannot be reached. Tax codes should be updated rapidly in order to avoid a permanent change of the tax law, which is costly both for the legislator and the taxpayers facing legal uncertainty.
Keywords: C73; H26; K34; 330; tax avoidance; tax evasion; population games